2008
DOI: 10.1002/ajh.21206
|View full text |Cite
|
Sign up to set email alerts
|

Reduced dose of lenograstim is as efficacious as standard dose of filgrastim for peripheral blood stem cell mobilization and transplantation: A randomized study in patients undergoing autologous peripheral stem cell transplantation

Abstract: In vitro studies have demonstrated a 27% increased efficacy of lenograstim over filgrastim. However, equal doses of 10 lg/kg/day of filgrastim and lenograstim have been recommended for mobilization of CD341 cells without associated chemotherapy. In this study, we investigated whether a 25% reduced dose of lenograstim at 7.5 lg/kg/day is equavalent to 10 lg/kg/day filgrastim for autologous peripheral blood stem cell (PBSC) mobilization and transplantation. A total of 40 consecutive patients were randomized to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…Despite these differences, Kopf et al evidenced a more rapid mobilization in patients receiving lenograstim (day median number ¼ 12) than in those receiving filgrastim (day median number ¼ 13), which is in line with our results. The randomized study by Ataergin et al 37 on patients with solid and hematological tumors agrees with our results, as it indicates that a lower dose of glycosylated G-CSF is as effective as the standard dose of non-glycosylated G-CSF for PBPC mobilization in patients undergoing auto-SCT.…”
Section: Treated With Lenograstimsupporting
confidence: 92%
“…Despite these differences, Kopf et al evidenced a more rapid mobilization in patients receiving lenograstim (day median number ¼ 12) than in those receiving filgrastim (day median number ¼ 13), which is in line with our results. The randomized study by Ataergin et al 37 on patients with solid and hematological tumors agrees with our results, as it indicates that a lower dose of glycosylated G-CSF is as effective as the standard dose of non-glycosylated G-CSF for PBPC mobilization in patients undergoing auto-SCT.…”
Section: Treated With Lenograstimsupporting
confidence: 92%
“…17,18) Furthermore, 25% reduction in the dose of Lenograstim (7.5 mg/kg/d) has an efficacy equivalent to 10 mg/kg/d of Filgrastim for autologous peripheral blood stem cell mobilization and transplantation. 19) Our results showed that ROS production by Lenograstim-induced mature neutrophils is higher than that by Filgrastim-induced mature neutrophils (Fig. 6B).…”
Section: Discussionmentioning
confidence: 49%
“…Although many reports compare and analyze these three types of rhGCSFs, [15][16][17][18][19] it remains unknown whether recovery from hematopoietic injuries by ionizing radiation depends on the type of rhG-CSF. In this study, we investigated the effects of these three different types of rhG-CSFs on human granulocyte progenitor cells and expansion of neutrophils from nonirradiated or X-irradiated human CD34 ϩ hematopoietic progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ria et al [18] found that lenograstim achieved the collection target more rapidly and with decreased leukapheresis compared with filgrastim using the same dose (10 μg/kg/day). Ataergin et al [26] found that 7.5 μg/kg/day lenograstim was as efficient as 10 μg/kg/day filgrastim. However, Kim et al [27] concluded that filgrastim significantly reduced the duration of neutropenia, thrombocytopenia, and days of G-CSF administration compared with lenograstim in patients undergoing peripheral blood stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%